TENDENCIES OF DISTANCE LEARNING DEVELOPMENT AT FOREIGN HIGHER SCHOOLS - Bohdan I. Shunevych (Інформаційні технології і засоби навчання, 2010)
The article deals with the tendency analysis of distance learning at higher educational schools of Europe and North America countries on the basis of two foreign researches with the article author’s participation.